1975
DOI: 10.1007/bf00132915
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Brassica pollen and expression of incompatibility in vitro

Abstract: Pollen derived from cabbage, broccoli, and collards (Brassica oleracea, var. capitata, Italica and acephala, respectively) will germinate in a synthetic medium consisting of sucrose, H3BO4, CaC12 and purified polyethylene glycol 20,000. The optimum levels of constituents varied from genotype to genotype. With one genotype of cabbage, a germination percentage of 84~,, and tube lengths of at least 3.5 mm long were obtained. Whereas pollen from broccoli germinated in 1 to 2 hours, cabbage pollen required a 3 to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

1980
1980
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 14 publications
1
16
1
Order By: Relevance
“…Regarding the effectiveness of the heat-treatment in overcoming inhibition by the diffusate on self-pollen, there is a similar report for Brassica (Ferrari and Wallace 1975) also obtained by testing self-pistil leachate in culture. The involvement of heat-labile substances in the incompatibility reaction, which has been observed here, agrees in turn with the well-known fact that temperature significantly affects plant incompatibility (see reviews by De Nettancourt 1977;Shivanna and Johri 1985).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Regarding the effectiveness of the heat-treatment in overcoming inhibition by the diffusate on self-pollen, there is a similar report for Brassica (Ferrari and Wallace 1975) also obtained by testing self-pistil leachate in culture. The involvement of heat-labile substances in the incompatibility reaction, which has been observed here, agrees in turn with the well-known fact that temperature significantly affects plant incompatibility (see reviews by De Nettancourt 1977;Shivanna and Johri 1985).…”
Section: Discussionsupporting
confidence: 51%
“…The following examples have been reported by HeslopHarrison (1983), who stressed, however, the difficulties in obtaining clear-cut effects in vitro: Petunia inflata and P. hybrida (Brewbaker and Majumder 1961 ;Sharma and Shivanna 1982), and Lilium longiflorum (Dickinson et al 1982). To this Offprint requests to: A. Speranza list, Brassica oleracea (Ferrari and Wallace 1975), Prunus avium (Williams et al 1982) and Nicotiana alata (Sharma and Shivanna 1985) should be added.…”
Section: Introductionmentioning
confidence: 99%
“…Recognition must therefore occur within minutes of pollination (Ferrari and Wallace, 1975). The events immediately following the first contact between the pollen grain and the stigma have thus drawn much interest.…”
mentioning
confidence: 99%
“…Suspension media composed of varying amounts of polyethylene glycol, calcium pectate, sodium caseinate or sodium alginate all reduced pollen viability, particularly after 1 h of drying. Ferrari & Wallace (1975) reported that germination of cabbage pollen was dependent on the presence of polyethylene glycol (M. Wt 20,(00) but we have been unable to repeat these findings with the pollens we have tested. However, suspension media composed ofCMC plus calcium nitrate and boric acid, partially maintained kiwifruit pollen viability after drying ( Fig.…”
Section: Discussionmentioning
confidence: 69%